Strukturalisme Genetik Lucien Goldmann dalam Novel Orang-Orang Proyek Karya Ahmad Tohari - Nurhasanah, Dewi (Bina Nusantara University, 2015)
Article clarified structure, global view of social class, and social structure function as the background of Orang-orang Proyek, a novel by Ahmad Tohari. Research applied analytic and dialectic descriptive method. Analysis was done by applying Genetic Structuralism theory by Lucien Goldmann to see the meaning of the novel by relating the structure of the novel with the human facts (social structure) as a background of the novel. The research results indicate that the novel structure described some oppositions, those are cultural, natural, social, and human oppositions; the novel?s structure expresses a global views, those are ideal-humanist and social-religious; when the novel was written, there were some corruption cases in the social structure in Indonesia that was adopted in the novel. Therefore, there seems a correlation between the novel structure and the social structure.